Semantics of the Birth Myth as a Cultural Code - Elena S. Stepanova (RUDN Journal of Language Studies, Semiotics and Semantics, 2024)
The study analyzes the birth myth from the symbolic point of view as a way to indicate the beginning of any existence, real or fictional: the birth of the Universe and a man, which sets out the primary understanding of the world and a man, time and space. The purpose of the analysis is to study the semantics of the birth myth, which reflects the archaic ideas of a person about birth, which made it possible to present the typology of the birth myth as a cultural code. The methodology of the study is based on the works by foreign and domestic scientists in the field of studying the notion “cultural code” as a semiotic system in linguoculturology and ethnolinguistics. The popular science works by Barbara S. Sproul “Primitive Myths. Creation Myths from Around the World” and “The Seeds of Life: From Aristotle to Da Vinci, From Sharks’ Teeth to Frogs’ Pants, the Long and Strange Quest Where Babies Come From” by Edward Dolnik, which contain a large collection of creation stories of the universe and a man, relating to the most different eras and cultures, including the ancient Egyptian and Hindu served as the material for the research. It shows that birth myths contain value orientations for representatives of a certain linguocultural society, which is manifested in cosmogonic, ritual, ancient and Bible myths. It analyses the means of representation of the birth myth as a cultural code. The given language means make possible to describe the process of birth more vividly and emotionally. It concludes that the birth myth represents a fragment of the linguistic view of the world through a mythological text, which helps introduce a man to sacred values that are inaccessible to human understanding, and besides the birth myth personifies natural phenomena, endowing them with anthropocentric properties.